Will Lynx Lose Their Edge? Canada Lynx Occupancy in Washington. Issue 4 (3rd March 2020) - King, Travis W.; Vynne, Carly; Miller, David; Fisher, Scott; Fitkin, Scott; Rohrer, John; Ransom, Jason I.; Thornton, Daniel
ABSTRACT: Populations of species located at southern range edges may be particularly vulnerable to the effects of climate change as warming temperatures and subsequent changes to ecosystems exceed species‐specific tolerances. One such species is Canada lynx ( Lynx canadensis ), a cold‐adapted mesocarnivore that maintains a large core population in Alaska, USA, and Canada but exists within several peripheral populations in the contiguous United States. Increases in temperature, declines in snow pack, and climate‐influenced increases in fire frequency and intensity, could negatively affect lynx populations, threatening their long‐term persistence in the continental United States. Despite these threats, our understanding of broad‐scale effects on lynx occupancy and the extent of current lynx distribution in many of these peripheral populations is minimal. We conducted an occupancy survey of lynx in Washington, USA, using a spatially extensive camera‐trapping array covering 7, 000 km 2 of potential lynx habitat. We used the resulting database of detection data to develop single‐season occupancy models to examine the abiotic and biotic effects on current lynx occupancy and predict future lynx distribution based on climate change forecasts. Our results show lynx occupancy across the Washington landscape is restricted and dictated largely by abiotic factors, disturbance regimes, and distance from source populations in Canada. Predictions of future distribution suggest lynx will be increasingly challenged by climatic changes, particularly at the southern and lower elevation portions of their range in Washington. Our results paint an alarming picture for lynx persistence in Washington that is relevant to current deliberations regarding lynx delisting from the Endangered Species Act. Our simple camera design was a highly effective method for surveying lynx across broad spatial scales, and could be a key monitoring tool for lynx that is easy to implement by researchers and government agencies. © 2020 The Wildlife Society. Abstract : Lynx occupancy across Washington state is highly restricted and dictated largely by abiotic factors, disturbance regimes, and distance from source populations in Canada with future predictions demonstrating a substantial potential northward retraction of lynx range in Washington by 2100. Understanding current occupancy patterns and factors influencing occupancy in Washington is particularly relevant in the broader context of ongoing discussions to remove lynx from listing in the Endangered Species Act.